2014
DOI: 10.14297/jpaap.v2i2.81
|View full text |Cite
|
Sign up to set email alerts
|

Do LEGO® Models Aid Reflection in Learning and Teaching Practice?

Abstract: In this paper we describe the use of LEGO® models within assessment of the Postgraduate Certificate in Academic Practice (PGCAP) offered at the University of Salford. Within the context of the PGCAP, we model innovative and contextualised assessment strategies for and of learning. We challenge our students, who are teachers in higher education (HE), to think and rethink the assessment they are using with their own students. We help them develop a deeper understanding and experience of good assessment and feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…However, the method itself may be seen as inappropriate for higher education and therefore resist it by students and/or supervisors. These observations are in line with James (2015) study that showed that especially in the context of doctoral level work, some individuals may find the use of LSP patronising; similar resistance to participation was reported in Nerantzi and Despard (2014) in an academic development application. In this study the experiences of facilitators of LSP were studied and therefore the picture and explanation of any possible resistance has been reported through their descriptions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the method itself may be seen as inappropriate for higher education and therefore resist it by students and/or supervisors. These observations are in line with James (2015) study that showed that especially in the context of doctoral level work, some individuals may find the use of LSP patronising; similar resistance to participation was reported in Nerantzi and Despard (2014) in an academic development application. In this study the experiences of facilitators of LSP were studied and therefore the picture and explanation of any possible resistance has been reported through their descriptions.…”
Section: Discussionsupporting
confidence: 87%
“…Gauntlett (2007) recognises that LSP can be a vehicle to share experiences, knowledge but also emotions. The emotions often present in LEGO workshops include openness, excitement and calmness but also anxiety and initial panic (Nerantzi and Despard, 2014). It is this opening up and the shared experience enabled through LSP that may make this method attractive in the context of doctoral supervision and doctoral researchers' and supervisors' development as it helps participating individuals to gain insights into the their relationships with the doctoral process, the doctoral research and each other.…”
Section: Lego ® Serious Play ® As An Affective Experience In Doctoralmentioning
confidence: 99%
“…The study emphasized reflective conversations via storytelling using LEGO ® bricks in a group discussion setting; this promoted reflections on experiences between group members (Peabody and Noyes, 2017). Nerantzi and Despard (2014) have investigated the use of LSP as an evaluation method in the context of professional discussion, and they reported that "the LEGO® models seem to have made a real difference to the depth of reflection, meaning-making and communicating learning" (p. 34).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that LSP is fundamentally based on several educational theories, there are just a handful of reports on using LSP in the context of education. LSP has been applied in a few higher education areas: reflecting on their learning process by creative arts students [7], fostering creativity of students studying management information systems [17], team building in a graduate information technology program [23] and engineering [1], developing assessment strategies by students in a postsecondary teacher education program [16], and leadership development in an industrial engineering program [8]. The majority of these reports do not indicate that LSP was used to teach students the 'core' topics of the corresponding courses or programs.…”
Section: Lsp and Software Engineeringmentioning
confidence: 99%